Minimalism and Expressivism - McDonald, Fritz (ETHICS IN PROGRESS, 2012)
There has been a great deal of discussion in the recent philosophical literature of the relationship between the minimalist theory of truth and the expressivist metaethical theory. One group of philosophers contends that minimalism and expressivism are compatible, the other group contends that such theories are incompatible. Following Simon Blackburn (manuscript), I will call the former position ‘compatibilism’ and the latter position‘incompatiblism.’ Even those compatibilist philosophers who hold that there is no conflict or tension between these two theories—minimalism and expressivism—typically think that some revision of minimalism is required to accommodate expressivism. The claim that there is such an incompatibility, I will argue, is based on a misunderstanding of the historical roots of expressivism, the motivations behind the expressivist theory, and the essential commitments of expressivism. I will present an account of the expressivist theory that is clearly consistent with minimalism.